PENGARUH WORK-LIFE BALANCE, EMPLOYEE ENGAGEMENT, DAN BURNOUT TERHADAP TURNOVER INTENTION PADA KARYAWAN GENERASI – Z DI BANDA ACEH - Nurkhafifah, Siti; Umar, Zulkifli; Sulfitra (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to identify the extent to which work-life balance, employee engagement, and burnout influence turnover intention among Generation Z employees in Banda Aceh. This research adopts a quantitative approach using a survey method, with questionnaires distributed to 100 respondents. The collected data were analyzed using multiple linear regression. The results show that work-life balance and employee engagement have a negative and significant effect on turnover intention, while burnout has a positive and significant effect. This means that better work-life balance and employee engagement tend to reduce the intention to resign, whereas high levels of burnout increase the desire to leave the job. Therefore, companies need to pay close attention to these factors in order to retain Generation Z employees and reduce turnover intention.